The Habsburg Monarchy's Many-Languaged Soul Translating and interpreting, 1848-1918 - Wolf, Michaela (John Benjamins Publishing Company, 2015)
This book traces translation and interpreting practices in the Habsburg Empire's (1848-1918) administration, courts and diplomatic service, and takes account of the "habitualised" translation carried out in everyday life. It then details the flows of translation among the Habsburg crownlands and between these and other European languages, with a special focus on Italian-German exchange. Applying a broad concept of "cultural translation" and working with sociological tools, the book addresses the mechanisms by which translation and interpreting constructs cultures, and delineates a model of the Habsburg Monarchy's "pluricultural space of communication" that is also applicable to other multilingual settings. German version of the book: http://e-book.fwf.ac.at/o:18